Multi-Hazard Vibration Control of Transmission Infrastructure: A Pounding Tuned Mass Damper Approach with Lifelong Reliability Analysis - Zhuoqun Zhang; Lizhong Qi; Jingguo Rong; Yaping Zhang; Peijie Li; Ziguang Jia (Buildings)
Power transmission tower-line systems are exposed to various dynamic hazards, including wind and earthquakes, among others. Despite the multitude of dampers proposed to mitigate vibrations, the dual control effect on both seismic and wind-induced vibrations has rarely been addressed. This paper introduces a comprehensive methodology for evaluating the reliability of power transmission towers under a range of dynamic disasters, encompassing both earthquakes and wind loads. Subsequently, a lifelong reliability approach was employed to assess the efficacy of a pounding tuned mass damper (PTMD). The proposed algorithm leverages the incremental dynamic analysis (IDA) method to compute structural fragility with regard to each type of disaster and integrates these findings with hazard functions to determine the probability of overall failure. The results conclusively demonstrate that the PTMD substantially diminished the towers’ dynamic response to both earthquakes and wind loads, thereby enhancing their overall reliability. Specifically, the PTMD reduced the vibration reduction ratio by 10% to 30% under wind loads and by 20% to 80% under seismic actions, with more pronounced effects at higher wind speeds and peak ground accelerations (PGAs). Furthermore, the reliability index (β) of the transmission tower increased from 2.1849 to 2.4295 when the PTMD was implemented, highlighting its effectiveness in dual-hazard scenarios. This study underscores the potential for reliability to be considered as a key metric for optimizing damping devices in power transmission structures, particularly in the context of multi-hazard scenarios.